Investigation of a group of Iranian theater artists' mental health and attitude toward patients with mental disorders - Negin Eissazade; Zahra Aeini; Rozhin Ababaf; Elham Shirazi; Mahsa Boroon; Hesam Mosavari; Adele Askari-Diarjani; Ala Ghobadian; Mohammadreza Shalbafan (Frontiers Media S.A., 2022)
IntroductionStigmatizing attitude toward patients with severe mental disorders is one of the main obstacles of improving the mental health of societies. Media plays an important role in how the public views mental health issues. Thus, we have performed this study to investigate the Iranian theater artists' mental health status, and their view toward patients with severe mental disorders.MethodsThis cross-sectional study was performed via an online anonymous survey including the Social Distance Scale and the Dangerousness Scale measuring the attitude of participants toward patients with severe mental disorders, and the 28-item General Health Questionnaire (GHQ-28). It was disseminated to artists who had the experience of working in theater in the past year in Iran.ResultsOur survey was responded by 104 artists. Social Distance Scale scores' mean was 10.67 (scores can range from 0 to 21) and the Dangerousness Scale scores' mean was 28.87 (scores can range from 8 to 56); higher scores indicate worse discrimination. Our participants' strongest fears were to let someone with a severe mental disorder to take care of their children, and for these groups of patients to obtain a hunting license. Twenty-six (25%) participants were at risk of moderate to severe anxiety, and 18 (17.3%) participants were at risk of moderate to severe depression.ConclusionBy and large, our participants did not have a positive attitude toward patients with severe mental disorders. Providing the knowledge of mental health issues can help the general public to be more tolerant of the mentally ill and specifically, theater can be employed to fight stigmatizing mental health issues by educating its audience.